Comparative study on maternal and fetal outcome in pregnant women with rheumatic heart disease and severe mitral stenosis undergoing percutaneous balloon mitral valvotomy before or during pregnancy - Sharma, J.B. (Indian Heart J, 2018)
INTRODUCTION: Mitral stenosis due to rheumatic heart disease is a common problem in India causing significant morbidity and mortality. We have compared the maternal and fetal outcome of women with severe mitral stenosis undergoing percutaneous balloon mitral valvotomy before or during pregnancy. METHODS: A total of 24 women of severe rheumatic mitral stenosis who underwent balloon mitral valvotomy before pregnancy (14 women, group 1) or during pregnancy (10 women, group 2) were included in the retrospective descriptive analysis. RESULTS: The mean age was 25.5 ± 3.6 yrs in group 1 and 25.7 ± 3.5 yrs in group 2. There was no difference in characteristics –primigravidas, time since diagnosis from pregnancy, NYHA (New York Heart Association) class and associated medical problems in the two groups. There was significant difference in cardiac events during pregnancy in the two groups. New York Heart Association class deterioration was observed in only 3(21.4% women in group 1) as compared to all (10; 100% women) in group 2(p < 0.001). The incidence of arrhythmias and atrial fibrillation was not different in two groups. Obstetric events were similar in the two groups. Mode of delivery and caesarean section rate was also similar in the two groups. There was no significant difference in mean birth weights (2399.75 ± 601.8 gm vs. 2641.70 ± 580.6 gm),rate of fetal growth restriction, still birth and congenital malformation rates in the two groups. CONCLUSION: Percutaneous mitral valvotomy for patients with severe mitral stenosis can be safely performed during pregnancy and has equivalent maternal and fetal outcomes as that performed before pregnancy.